ChemInform Abstract: One‐Pot Synthesis of Functionalized β‐Amino Sulfides/β‐Amino Selenides via Ring Opening of Cyclic Sulfamidates. Issue 11 (March 2015) - Venkateswarlu, Cheerladinne; Datta, Bandita; Chandrasekaran, Srinivasan
Abstract In—situ formed thiolate ions from rongalite react in a highly stereospecific manner at the C—O bond yielding enantiopure products in good to excellent yields.